Direct and Indirect Effects of Third-Party Relationships on Interpersonal Trust - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2006)
Past studies of the determinants of interpersonal trust have focused primarily on how trust forms in isolated dyads. Yet within organizations, trust typically develops between individuals who are embedded in a complex web of existing and potential relationships. In this article, the authors identify 3 alternative ways in which a trustor and trustee may be linked to each other via third parties: network closure (linked via social interactions with third parties), trust transferability (linked via trusted third parties), and structural equivalence (linked via the similarity of their relationships with all potential third parties within the organization). Each of these is argued to influence interpersonal trust via a distinct social mechanism. The authors hypothesized that network closure and structural equivalence would predict interpersonal trust indirectly via their impact on interpersonal organizational citizenship behaviors performed within the interpersonal relationship, whereas trust transferability would predict trust directly. Social network analyses of data gathered from a medium-sized work organization provide substantial support for the hypotheses and also suggest important directions for future research. (PsycINFO Database Record (c) 2008 APA, all rights reserved)(from the journal abstract)